Knowledge sharing intention at the workplace : a case study in a selected bank in Malaysia - Irwan Shahrani Bin Hassan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
The rapid growth of the financial industry is putting a demand on banks to look for better ways to manage its corporate strategies. One of the ways to achieve that aim is through knowledge management. This mix-method research investigated knowledge sharing (KS) intention and behaviour as part of the corporate strategies in a prominent Malaysian government-linked financial institution, Bank Co. Both quantitative and qualitative approaches were utilised during the data collection process, which consisted of questionnaire survey, focus group discussions, and a review of the organisation's documents on knowledge management. In-depth perceptions among Bank Co. staffs were explored that covered four main areas, namely knowledge sharing intention, workplace emotions, attitudes and Islamic Work Ethic (IWE). The questionnaire survey was used to identify pertinent categories related to the phenomenon of interest while focus group discussions and document review provided the in-depth analysis of the actual knowledge sharing intention and behaviour within Bank Co. The research involved 308 respondents in the survey and 27 participants in the focus group discussions. The quantitative data was analysed using descriptive statistical analysis while the qualitative data was analysed using content analysis. Two main theories were used as the framework for this research. The main theory, Knowledge Creation Theory (KCT), highlighted the main concern of this current research, which is the knowledge creation processes in the organisation which includes the employees' KS intention. Meanwhile, the Affective Event Theory (AET) was used to identify the themes related to workplace emotions, which influenced the attitudes towards KS intention at the workplace. In this research, the established preposition was Islamic Work Ethic (IWE) can encourage the knowledge sharing intention and behaviour of the Muslim workers regardless of the workplace associated emotions. The conclusions based on the findings of this research indicated that the staffs' perceived KS behaviours in Bank Co. were influenced by emotions and attitudes assessments of the individual. Bad events at the workplace resulted in a more negative assessment of the KS behaviours. However, observing the Islamic faith and ethics could potentially promote positive KS behaviours in Bank Co. regardless of the individual's emotions and attitudes assessment of the conditions. In term of methodology, this research added new perspectives to theories related to KS at the workplace as well as provided a foundation for discussing government agencies' treatment of KS. This discussion may encourage reforms of the existing knowledge management structures and practices. In addition, this research could serve as a basis for future research in this area, not just within the government-linked banks but other industries as well. From the practical perspective, this research provided Bank Co. with the opportunity to better understand to what extent their KS initiatives have succeeded. This can assist Bank Co. in designing programmes that can encourage productive KS behaviours within the organisation.